2017
DOI: 10.1016/j.foodhyd.2017.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical and viscoelastic properties of high pressure homogenized lemon peel fiber fraction suspensions obtained after sequential pectin extraction

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 48 publications
4
64
1
Order By: Relevance
“…An acid extraction was performed to remove pectin from the AIR according to the protocol described by Willemsen et al (2017). In particular, 60 g of AIR was suspended in 4000 ml of distilled water and incubated for 30 min at 80 °C under stirring.…”
Section: Lemon Peel Acid Insoluble Residuementioning
confidence: 99%
See 3 more Smart Citations
“…An acid extraction was performed to remove pectin from the AIR according to the protocol described by Willemsen et al (2017). In particular, 60 g of AIR was suspended in 4000 ml of distilled water and incubated for 30 min at 80 °C under stirring.…”
Section: Lemon Peel Acid Insoluble Residuementioning
confidence: 99%
“…Recent work of Willemsen et al (2017) showed that extensive pectin extraction, performed under alkaline (pH 10) or acid (pH 2.5) conditions, favors the viscoelastic properties (i.e. storage modulus) of lemon peel fiber suspensions differently.…”
Section: Effect Of Homogenization Pressurementioning
confidence: 99%
See 2 more Smart Citations
“…Xu et al [ 45 ] indicated that for the preparation of soluble peach fiber from fresh peach marc, it must be dispersed in three times the volume of deionized water, thus improving the efficiency of cellulose hydrolysis. For pectin extraction from milled dried lemon peel, variations in dilutions changed the properties of the extracted pectin, resulting in residues with different pectic characteristics [ 46 ]. Discarded external lettuce leaves were dispersed in hydroalcoholic solutions and polyphenols extracted with ethanol to obtain good phenolic extraction yields [ 47 ].…”
Section: Extraction and Technological Functionality Improvement Ofmentioning
confidence: 99%